An Approach of Brain-Computer Interface Electroencephalography for Measuring Visual Height Intolerance - Moch Yusuf Asyhari; Dhomas Hatta Fudholi; Fery Luvita Sari (JUITA : Jurnal Informatika, 2021)
The environment is one factor that influences the quality of life, including a high environment for people with the fear of height (Visual Height Intolerance, VHI). Currently, VHI is measured by using the Visual Height Intolerance Severity Scale (VHISS). The lack of evidence-based testing makes these measurements feel weak and less meaningful. The use of Virtual Reality (VR) and Electroencephalography (EEG) based on the Brain-Computer Interface (BCI) deserves to be tested. The test is done by reading the human brain's electrical activity using a BCI-based EEG when given VR exposure. The analysis process uses a simple wave concept. Furthermore, the correlation study was carried out using the Spearman-rho method with a consideration of the normality test, which produced non-parametric data. The correlation test results show that the BCI-based EEG biometric data in the form of the amount of waves per time and magnitude has a strong relationship with the VHISS scale. The higher the number of waves per time, the higher the amplitude, the higher the VHISS scale. The evaluation was carried out by examining the correlation based on the demographics of age and gender. Finally, EEG based on BCI and VR can be an alternative and concrete evidence to review the level of visual height intolerance other than VHISS.